Capital Structure and Firm’s Sustainability: Evidence from Malaysian Oil and Gas Companies at Bursa Malaysia - Hadi, Abdul Razak Bin Abdul (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study looks into how capital structure theories explain capital structure characteristics of oil and gas companies in Malaysia